Promising potential of articaine-loaded poly(epsilon-caprolactone) nanocapules for intraoral topical anesthesia. - Camila Batista da Silva; Maria Cristina Volpato; Bruno Vilela Muniz; Cleiton Pita Dos Santos; Luciano Serpe; Luiz Eduardo Nunes Ferreira; Nathalie Ferreira Silva de Melo; Leonardo Fernandes Fraceto; Francisco Carlos Groppo; Michelle Franz-Montan (PLoS ONE, 2021)
To determine whether the permeation capacity and analgesic efficacy of articaine (ATC) could be increased and cytotoxicity decreased by encapsulation in poly(ɛ-caprolactone) nanocapsules (ATCnano), aiming at local or topical anesthesia in dentistry. Cellular viability was evaluated (using the MTT test and fluorescence microscopy) after 1 h and 24 h exposure of HaCaT cells to ATC, ATCnano, ATC with epinephrine (ATCepi), and ATC in nanocapsules with epinephrine (ATCnanoepi). The profiles of permeation of 2% ATC and 2% ATCnano across swine esophageal epithelium were determined using Franz-type vertical diffusion cells. Analgesic efficacy was evaluated with a von Frey anesthesiometer in a postoperative pain model in rats, comparing the 2% ATC, 2% ATCnano, 2% ATCepi, and 2% ATCnanoepi formulations to 4% ATCepi (a commercially available formulation). We show that use of the nanocapsules decreased the toxicity of articaine (P<0.0001) and increased its flux (P = 0.0007). The 2% ATCepi and 4% ATCepi formulations provided higher analgesia success and duration (P<0.05), compared to 2% ATC, 2% ATCnano, and 2% ATCnanoepi. Articaine-loaded poly(ɛ-caprolactone) nanocapsules constitute a promising formulation for intraoral topical anesthesia (prior to local anesthetic injection), although it is not effective when injected in inflamed tissues for pain control, such as irreversible pulpitis.